«O Sancta Haera». Pilgrims and Pilgrimage in the Sanctuary of Sainte Foy at Conques - Marco Papasidero (Almatourism, 2017)
The Liber miraculorum Sancte Fidis, written during the XI century, partially by Bernard of Angers, describes miracles, healings and rituals practiced in the sanctuary of Sainte Foy at Conques, martyr of the beginning of the IV century.The Liber allows us to analyze the anthropological and religious dimension of the pilgrims and their pilgrimage. As a matter of fact, through the descriptions of the pilgrims, their gestures, their aspects, their words, their ritual practices by the tomb, their rich or poor offerings, we can analyze the dimension of the Medieval pilgrimage as a specific case study, which can help us describe the idea of pilgrimage in Medieval West Europe and specifically in this sanctuary.Furthermore, through the reading of the accounts of miracle stories, we can analyze the healing ritual practices, the miraculous dimension of this cult and the Sainte’s ability to treat diseases. The center of the Conques cult was – and remains – the Majesty of Sainte Foy, a reliquary statue in which the power (virtus/dynamis) of the saint’s relics is concentrated.